Electromyographic validation of the trapezius and serratus anterior muscles in military press exercises with open and middle grip - Büll, M. L. [UNESP]; Vitti, M. [UNESP]; Freitas, V. [UNESP]; Rosa, G. J M [UNESP] (My University, 2001)
Electromyographic activity of the trapezius muscle and serratus anterior muscle was analysed in 4 different modalities of military press exercises, each of them with 2 grips: open and middle. It was analyzed 24 male volunteers using a 2-channel TECA TE 4 electromyograph and Hewlett Packard surface electrodes. The TS and SI muscles acted with high and very high activity in all the modalities of military press exercises. Statistically, they did not show significative difference in the performance of the exercises with open and middle grip, justifying the inclusion of this group of exercises with both grips for the physical conditioning programmes.
Keywords: adult; back muscle; electrode; electromyography; exercise; hand grip; human; human experiment; joint mobility; male; military service; muscle action potential; muscle function; muscle strength; physical performance; sports medicine; trapezius muscle; Adolescent; Adult; Electromyography; Humans; Isometric Contraction; Male; Motor Neurons; Muscle, Skeletal; Weight Lifting